Models of Moderation based instructions in teaching English at Islamic Senior High Schools in Makassar - Pelu, Hanafie; Mahmud, Murni; Nur, Sahril; Salija, Kisman (Indonesian Journal of Educational Studies, 2021)
Abstract. Moderation is an important aspect in education since it can contribute to democratic education. Educational system in Indonesia needs to consider implementing the concept of moderation, especially in Islamic Schools. For this purpose, this research aims at exploring the models of moderation in Islamic Scools in Makassar. This research focuses on exploring the models of moderation based instruction in teaching English at Islamic Senior High School in Makassar. The subject of the study is an English teacher and the students of one islamic Senior High School in Makassar. This study employed an ethnographic research design. The researchers aaplied observation, interview, note taking, and documentation of English teacher in exploring the implementation of moderation based instruction in teaching English. Findings from this study shows that PELA Model which stands for Preparing material, Established and adopting the local wisdom, Learn to apply in ourselves before teaching others and Applicate imoderation based instruction in English teaching. This model is only suggested model that should be followed up by further research to examine and measure the effectiveness of this model. This study will contribute to the professional knowledge of how to implementation moderation in teaching English in Islamic Schools in Indonesia as well as providing insights for policy- making and improving the quality of primary-school level English language teaching in general.Keywords: Moderation; instruction; moderation-based instruction; English Language Teaching